Iowa RBA, March 3, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for March 3, 1997. Highlights of the update include the return of Killdeer and Red-winged Blackbirds to the state as well as the continued presence of Great Gray Owls and a Pinyon Jay. Other interesting observations were of a Snowy Owl, six Red Crossbills, and a first year Thayer's Gull. Also included are handwritten notes for the next week's update with sightings of a Brewer's Blackbird and a Barnacle Goose. Epson - sheet feed/flatbed